THE EFFECT OF USING GPT CHAT ARTIFICIAL INTELLIGENCES (AI) ON STUDENTS' HIGHER-ORDER THINKING SKILLS - Mariati, Mariati (Proceeding International Seminar of Islamic Studies, 2024)
Information and communication technology has evolved dramatically especially in recent decades, not least technology that affects learning in the world of education including in higher education. One of the technological innovations that appear and develop today is the use of artificial intelligence (AI) in the form of openAI chatbots, namely Chat GPT. The use of Chat GPT in the learning process raises pros and cons in learning because it has a complex impact. One of the impacts caused is the decline in the level of critical thinking skills and problem-solving abilities of students as one part of higher-order thinking skills in 21st century learning, namely critical thinking and problem solving. The purpose of this study was to determine the impact of using Chat GPT on the critical thinking skills of students, especially accounting education students at the Faculty of Teacher Training and Education, University of Muhammadiyah North Sumatra (FKIP-UMSU). The type of research used is qualitative research with an ethnographic approach. The population in this study was students of the accounting education study program in the third, fifth and seventh semesters with a sample of 30 students. Data collection techniques in this study used questionnaires, interviews and observations. The results showed that there was an influence of Chat GPT on students' critical thinking skills as an indicator of higher-order thinking skills.